Evolutionary Adaptations of Palmer Amaranth (Amaranthus palmeri) to Nitrogen Fertilization and Crop Rotation History Affect Morphology and Nutrient-Use Efficiency. Issue 2 (14th December 2017) - Bravo, Washington; Leon, Ramon G.; Ferrell, Jason A.; Mulvaney, Michael J.; Wood, C. Wesley
Abstract : Palmer amaranth control has become a major challenge for multiple cropping systems across the southeastern and midwestern United States. Despite extensive research on herbicide-resistance evolution, little research has been done exploring how Palmer amaranth might also be evolving other adaptive traits in response to different selection forces present in agricultural fields and the enrichment of soils with nutrients such as nitrogen. The objective of the present study was to determine whether Palmer amaranth populations have evolved different morphology and growth patterns in response to glyphosate use and fertilization history. Ten Palmer amaranth populations, including glyphosate-resistant (GR) and glyphosate-susceptible (GS) populations, were collected from different cropping systems with histories of high and low nitrogen fertilization in the states of Florida and Georgia. All populations were grown in pots filled with soil fertilized with either 0 or 40 kgNha −1, and their response to nitrogen was compared for morphological, growth, and nutrient-use traits. Populations differed in how they modified their morphology and growth in response to N, with major differences in traits such as foliar area, branch production, leaf shape, and canopy architecture. Populations with high nitrogen-fertilization histories had higher (>43%) nutrient-use efficiency (NUE) than populations with low nitrogen-fertilization histories. Similarly, GR populations have evolved higher NUE (>47%) and changed canopy architecture more than GS populations in response to nitrogen fertilization. The results of the present study highlight the importance of paying more attention to adaptations to cultural practices that might increase weediness and how genetic changes in traits involved in morphology and metabolism might favor compensatory mechanisms increasing the fitness of the population carrying herbicide-resistant traits.